2018
DOI: 10.1186/s12943-018-0869-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of hypoxia-induced exosomes in tumor biology

Abstract: PurposeHypoxia is a major regulator of angiogenesis and always influences the release of exosomes in various types of tumors. The present review aimed to assess the role of hypoxia-induced exosomes in the tumor biology.MethodsThe relevant publications were retrieved from PubMed using keywords such as hypoxia, exosome, extracellular vesicles, tumor, cancer, and other similar terms.ResultsRecent studies have shown that cancer cells produce more exosomes under hypoxic conditions than do parental cells under normo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
203
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(209 citation statements)
references
References 79 publications
4
203
0
2
Order By: Relevance
“…Rapid cell proliferation and insufficient oxygen supply due to increased oxygen demand and slow new vascularization network formation develop a hypoxic microenvironment in the most solid tumors. This hypoxic microenvironment with low nutriment regulates behaviors, differentiation, and function of TME cells such as tumor cells, inflammatory immune cells, and stromal cells . Tumor‐infiltrating lymphoid cells, tumor‐associated macrophages (TAMs), dendritic cells, myeloid‐derived suppressor cells represent the most important immune cells in TME.…”
Section: Exosomes In Hypoxia Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid cell proliferation and insufficient oxygen supply due to increased oxygen demand and slow new vascularization network formation develop a hypoxic microenvironment in the most solid tumors. This hypoxic microenvironment with low nutriment regulates behaviors, differentiation, and function of TME cells such as tumor cells, inflammatory immune cells, and stromal cells . Tumor‐infiltrating lymphoid cells, tumor‐associated macrophages (TAMs), dendritic cells, myeloid‐derived suppressor cells represent the most important immune cells in TME.…”
Section: Exosomes In Hypoxia Conditionsmentioning
confidence: 99%
“…Tumor‐infiltrating lymphoid cells, tumor‐associated macrophages (TAMs), dendritic cells, myeloid‐derived suppressor cells represent the most important immune cells in TME. Exosomes secreted from TME cells under hypoxia can regulate tumor growth, development, progression, angiogenesis, and immune responses in a direct or indirect manner (Table ) …”
Section: Exosomes In Hypoxia Conditionsmentioning
confidence: 99%
“…It is demonstrated that tumour cells increase the release of MVs with enhanced procoagulant activity . Hypoxia induced more exosomes production in tumour cells and play important roles in tumour angiogenesis, invasion, metastasis and the immune system . It is likely that cells subjected to stress increase its communication with adjacent cells via the release of EVs …”
Section: Generation and Properties Of Extracelluar Vesicle (Ev)mentioning
confidence: 99%
“…2 Hypoxia induced more exosomes production in tumour cells and play important roles in tumour angiogenesis, invasion, metastasis and the immune system. 3 It is likely that cells subjected to stress increase its communication with adjacent cells via the release of EVs. 4 During secretion, EVs contain endogenous substances from the parent cells, including RNAs, DNAs, proteins and lipids.…”
mentioning
confidence: 99%
“…Tumor‐derived EVs contain proteins and nucleic acids, which serve as key mediators of cellular communication, promoting tumor progression and treatment resistance . Hypoxic cells release numerous EVs which have been shown to mediate multiple regional and systemic effects, such as local neovascularization and invasiveness as well as distant organ metastasis . MicroRNAs (miRNAs) are non‐coding small RNA molecules that regulate gene expression at the post‐transcriptional/translational level.…”
Section: Introductionmentioning
confidence: 99%